Rura Uderzeniowa, Pomiary i Wnioski - Z.A. Walenta; T.T. Rudowska (Engineering Transactions)
The present paper contains theoretical investigations concerning the possibility and sense of applying a shock tube to aerodynamic investigations (as a wind tunnel of very short working period), a description of the shock-tube constructed for the Department of Mechanics, IBTP P.A.S. and, finally, the results of preliminary tests carried out by means of this tube. It is found that the quality of the tube is the same as that of other tubes of the same type. The tube and its measuring equipment enables the investigation of certain fundamental phenomena. In view of the growing interest in gas flow at elevated temperatures (chemical reactions and ionization phenomena being accounted for) it is necessary a to build a new tube, enabling these phenomena to be produced.